Otoscopic evaluation of epithelial remnants in the tympanic cavity after total ear canal ablation and lateral bulla osteotomy. Issue 7 (27th July 2020) - Watt, Meghan M.; Regier, Penny J.; Ferrigno, Cassio R. A.; McConkey, Marina J.; Fox‐Alvarez, W. Alexander; Bertran, Judith
Abstract: Objective: To determine the ability to detect the presence of epithelial remnants after total ear canal ablation (TECA) and lateral bulla osteotomy (LBO) with endoscopy and to identify the most common locations of epithelial remnants after tympanic curettage. Study design: Experimental study. Animals: Five fresh canine cadavers with no gross evidence of middle ear disease. Methods: Ten TECA‐LBO were performed by four surgeons. After tympanic curettage, a 1.9‐mm rigid 30° endoscope was inserted into the rostral, caudal, dorsal, ventral, and medial sections of the tympanic cavity. Three observers evaluated otoscopic images for epithelial remnants in each compartment. The median distribution of epithelial remnants was calculated for each section of the tympanic cavity with a three‐dimensional tympanic cavity model. Results: Epithelial remnants were identified in at least one of the five areas of the tympanic cavity after each TECA‐LBO. The rostral section contained the most epithelial remnants (35.6%), while the medial section contained the least amount (1.8%). Conclusion: Use of a 1.9‐mm rigid endoscope was an effective method to evaluate all sections of the tympanic cavity after curettage in TECA‐LBO. Epithelial remnants were consistently found after TECA‐LBO, especially in the rostral compartment. Clinical significance: Intraoperative endoscopy should be considered to improve removal of epithelium after initial TECA‐LBO or revision surgeries.